Early-stage inflammation and experimental therapy in transgenic models of the Alzheimer-like amyloid pathology - Cuello, A.C. (2010)
Background: Intracellular accumulation of β-amyloid (Aβ) is one of the early features in the neuropathology of Alzheimer's disease (AD) and Down's syndrome. This can be reproduced in cell and transgenic animal models of the AD-like amyloid pathology. In a transgenic rat model, our lab has previously shown that the intracellular accumulation of Aβ is sufficient to provoke cognitive impairments and biochemical alterations in the cerebral cortex and hippocampus in the absence of amyloid plaques. Objective: To investigate an early, pre-plaque inflammatory process in AD-like transgenic models and establish whether the neurotoxic effects of Aβ oligomers and proinflammatory responses can be arrested with minocycline. Methods: For these studies, we used naïve mice and transgenic animal models of the AD-like amyloid pathology and applied neurochemical, immunohistochemical and behavioral experimental approaches. Results: In the early stages of the AD-like amyloid pathology, intracellular Aβ oligomers accumulate within neurons of the cerebral cortex and hippocampus. Coincidental with this, behavioral impairments occur prior to the appearance of amyloid plaques, together with an upregulation of MHC-II, i-NOS and COX-2, well-known proinflammatory markers. Treatment with minocycline corrected behavioral impairments, lowered inflammatory markers and levels of Aβ trimers. Conclusion: A pharmacological approach targeting the early neuroinflammatory effects of Aβ might be a promising strategy to prevent or delay the onset of AD.